Progressive multifocal leucoencephalopathy with unusual inflammatory response during antiretroviral treatment. Issue 8 (21st July 2003) - Hoffmann, C; Horst, H-A; Albrecht, H; Schlote, W
Abstract : A case of biopsy verified progressive multifocal leucoencephalopathy (PML) in an HIV patient is presented. Imaging and histological examination confirmed remarkable inflammatory activity accompanied by an unusually benign clinical course despite no clear evidence of immune reconstitution after the start of antiretroviral treatment. This case not only raises several questions regarding the pathophysiology of PML, but gives also evidence that AIDS associated inflammatory PML must be considered another clinical entity in the expanding range of diseases now commonly referred to as the immune reconstitution syndrome.